Long-term outcomes of spinal meningioma resection with outer layer of dura preservation technique. (January 2021) - Saiwai, Hirokazu; Okada, Seiji; Hayashida, Mitsumasa; Harimaya, Katsumi; Matsumoto, Yoshihiro; Kawaguchi, Ken-ichi; Iida, Kei-ichiro; Kobayakawa, Kazu; Yokota, Kazuya; Maeda, Takeshi; Tsuchiya, Kuniyoshi; Arizono, Takeshi; et al.
Highlights: Dural reconstruction is not necessary for dura preservation technique. Tumor recurrence rate was 8.3% (1 of 12 cases) in dura preservation technique. Recurrence was identified 141 months after resection by dura preservation technique. Abstract: Spinal meningioma is a common benign intradural spinal tumor. It has been reported that the local recurrence rate after surgical resection increases with longer follow-up duration. Simpson grade 1 resection could reduce the risk of recurrence, but this procedure needs dural reconstruction, which would cause cerebrospinal fluid (CSF) leakage or iatrogenic spinal cord injury. Saito et al. reported dura preservation technique to reduce the risk of CSF leakage, in which the meningioma together with the inner layer of the dura is removed and the outer layer is preserved for simple dural closure. The long-term outcomes with this technique have never been investigated. In this study, we retrospectively analyzed the data of 38 surgically treated patients (dura preservation technique, 12 patients; Simpson grade 2 resection, 26 patients) to assess the long-term recurrence rate (mean, 121.5 months; range, 60–228 months). The local recurrence rate in the dura preservation group was 8.3% (1 of 12 cases), which was similar to that in Simpson grade 2 resection group (2 of 26 cases [7.7%]). Although this case series did not indicate the significant difference in the recurrence rates between the dura preservation group and Simpson grade 2 group, we consider that this technique still has advantages for surgically less invasiveness in terms of dural reconstruction which is necessary for Simpson grade 1 and higher possibility of complete resection of tumors compared with Simpson grade 2 resection.